A literature review: Geography learning based on microlearning to increase student’s ecoliteracy - Wijaya Nyokro Mukti; Kastolani Wanjat; Yani Ahmad (E3S Web of Conferences)
Geography teachers find the difficulty to use geography learning to increase the students’ ecoliteracy because the scope of geography subjects is very wide. In fact, ecoliteracy is a provision for students to overcome environmental problems that are getting worse. Therefore, this study aims to design geography learning based on microlearning to increase students’ ecoliteracy. The method used is a literature review with descriptive analysis. The results of the research are the design of geography learning based on microlearning which includes (1) mapping of ecoliteracy microcontent in geography learning, (2) implementation of geography learning based on microlearning, and (3) geography learning media based on microlearning to Increase ecoliteracy. The conclusion is that geography learning based on microlearning needs to facilitate geography teachers in utilizing geography learning to Increase students’ ecoliteracy.